Diseño e implementación de un sistema de gestión de calidad en el proceso de producción basado en las normas ISO 9000:2000 para la empresa ANILEC S.A - Díaz Albán, Nelson Rodrigo (2011)
This work concerns the design level and implementation of a quality management system based on ISO 9000: 2000 and consists of five chapters: Overview, total quality management, processes for quality policy ANILEC CA, Preparation of documentation for quality management system for the company ANILEC CA based on the ISO 9000: 2000, conclusions and recommendations. The basic concepts that manifest before entering the central theme, from administrative terms are closely linked to quality.